2015
DOI: 10.1371/journal.pone.0129024
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Neural Network Stratifies the Risks of Reintervention and Mortality after Endovascular Aneurysm Repair; a Retrospective Observational study

Abstract: BackgroundLifelong surveillance after endovascular repair (EVAR) of abdominal aortic aneurysms (AAA) is considered mandatory to detect potentially life-threatening endograft complications. A minority of patients require reintervention but cannot be predictively identified by existing methods. This study aimed to improve the prediction of endograft complications and mortality, through the application of machine-learning techniques.MethodsPatients undergoing EVAR at 2 centres were studied from 2004-2010. Pre-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 46 publications
0
34
0
1
Order By: Relevance
“…Different studies indicated that ANN models can simultaneously process numerous variables and can consider outliers and nonlinear interactions among variables. Therefore, whereas conventional statistics reveal parameters that are significant only for the overall population, the ANN model includes parameters that are significant at the individual level even if they are not significant in the overall population [1316]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies indicated that ANN models can simultaneously process numerous variables and can consider outliers and nonlinear interactions among variables. Therefore, whereas conventional statistics reveal parameters that are significant only for the overall population, the ANN model includes parameters that are significant at the individual level even if they are not significant in the overall population [1316]. …”
Section: Discussionmentioning
confidence: 99%
“…Artificial neural networks (ANN) have been used to predict the risk of post-operative events, including survival, exploring complex relationships between preoperative variables survival in different surgical settings and are increasingly being used in complex medical decision making [1316]. …”
Section: Introductionmentioning
confidence: 99%
“…Further complex concerns such as endograft configuration and deployment, or intermediate markers of patients’ cardiovascular risk phenotype, could possibly be used to train ANN in prospective studies, which increases the clinical significance of prediction and makes it more reliable. Also, adding more operative factors such as graft size, and endoleak at completion or post-operative variables, such as endoleak at early surveillance scans, could significantly enhance the discriminatory power of ANNs [ 61 ]. As an evidence, the proposed FS approach using ANN has selected maximum aneurysm neck diameter, diameter of the left common iliac artery 1 and 5 mm below internal iliac ostium, maximum common iliac artery diameter 5 mm proximal to internal iliac origin, maximum iliac tortuosity index, maximum common iliac thrombus volume, and right common iliac artery non luminal volume.…”
Section: Discussionmentioning
confidence: 99%
“…In the researcher’s previously published paper [ 60 ], an uncensoring approach was proposed to deal with the high level of censoring in the EVAR datasets using MLT without performing FS. Moreover, in the researcher’s other publication [ 61 ], the proposed uncensoring approach was combined with an existing ranking FS method to reduce the number of features in the datasets. Factor analysis is a feature transformation method used to transform data into a new domain so that most of the classification related information is compressed in a smaller number of features [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parallel topology is the most common way used to connect classifiers [48], so it is adopted in this paper.…”
Section: Multiple Classifiers Systemmentioning
confidence: 99%